2020
DOI: 10.12669/pjms.36.4.1642
|View full text |Cite
|
Sign up to set email alerts
|

Do you really get what you are looking for? Exploring the medical call writing trend in tertiary care hospitals

Abstract: Objective: To explore the trend of medical call writing by doctors working in tertiary care hospitals. Methods: A quantitative descriptive cross-sectional study was carried out to evaluate the quality of medical calls written by the doctors at three tertiary care hospitals of Peshawar, Khyber Pakhtunkhwa between June 2016 to June 2017. An instrument was developed following AMEE Guide 87. Its content validity and reliability were established by 33 consultants from twenty specialties. A total of 198 medica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 10 publications
1
2
0
Order By: Relevance
“…A study conducted in Khyber Medical University to explore the trend of medical call writing by doctors working in tertiary care hospitals, concluded that the content of medical calls was found to be inadequate. 11 Similar observations were made in the present study. This was probably because medical colleges and training programmes focus on patient diagnosis, management and bedside manners, but do not include any emphasis on effective communication between physicians.…”
Section: Discussionsupporting
confidence: 92%
“…A study conducted in Khyber Medical University to explore the trend of medical call writing by doctors working in tertiary care hospitals, concluded that the content of medical calls was found to be inadequate. 11 Similar observations were made in the present study. This was probably because medical colleges and training programmes focus on patient diagnosis, management and bedside manners, but do not include any emphasis on effective communication between physicians.…”
Section: Discussionsupporting
confidence: 92%
“…Several authors [5][6][7][8][9][10][11][12][13] including Osinaike et al [1] in Lagos reported that referral letters received were poorly written and with significant information about patient care frequently missing. The information commonly documented as missing in the referral letters included identity of the writers, the patients' age and gender, the treatment given, the findings from the investigations performed, the medical history and what the writers expect from the referral.…”
Section: Introductionmentioning
confidence: 99%
“…The information commonly documented as missing in the referral letters included identity of the writers, the patients' age and gender, the treatment given, the findings from the investigations performed, the medical history and what the writers expect from the referral. Other commonly missing information included examination findings, provisional diagnosis, history of presenting complaints, writers' addresses, reasons for the referral and patients' names [5][6][7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%